An agent-based approach to group decision simulation using argumentation - Neves, José (2006)
Group decision making simulation allows for the creation of virtual group decision scenarios. The use of a group decision simulator enhances user competences in this area, to test different argumentation strategies and to validate “what if” useful real world scenarios. In this paper, it is proposed a multiagent model to simulate group decision making tasks. Agents are designed with emotional properties, reason with incomplete information and use persuasive argumentation to convince the other group elements about the best alternative choice.